Chemical Constituents, Antioxidant Activities, and Element Concentrations of Rusa Deer Velvet Antler Extracts. (15th October 2020) - Limmatvapirat, Chutima; Rodhetbhai, Potcharet; Somsakraksanti, Krittaphas; Danpongprasert, Pitcha; Poonsub, Soranun; Krongrawa, Wantanwa; Limmatvapirat, Sontaya; Meepan, Maneerat
Abstract : The objective of this study was to analyze hexane extract (HE), 75% v / v ethanol extract (EE), and water extract (WE) of rusa deer velvet antlers, obtained through a three-solvent sequential extraction, for determining their chemical constituents, antioxidant activities, element concentrations, and microbial contamination. In TLC, FTIR, 1 H NMR, and HPLC analysis, HE and EE showed the presence of oleic acid, linoleic acid, alpha-linolenic acid, and testosterone. EE showed the highest concentration of testosterone and the strongest antioxidant activity in DPPH and FRAP assays. In addition, the concentration of testosterone in EE was higher than in sika deer and red deer velvet antler extracts found in other studies. All extracts were composed of essential elements and had levels of toxic elements and microbial contaminants lower than the acceptable criteria set by ASEAN guidelines. Thus, EE was considered to be a safe and useful source of antioxidants and testosterone.